Development of Worksheets on Creative Product Learning and Entrepreneurship in Indonesia’s Vocational Education & Training Schools - Yuliyah Yuliyah; Budi Santosa (Universitas Ahmad Dahlan, 2022)
This research is a research and development (R & D) that aims to analyse and develop Problem-Based Student Activity Sheets/PBSAS using android in the subjects of Creative Products Learning and Entrepreneurship (CPLE) in Vocational Education & Training/VET School that meets the proper and effective requirements. The development of PBSAS using the ADDIE model includes analysing, designing, developing, implementing, and evaluating. Research location conducted at VET School Negeri 2 Cilacap with sample study participant educate XI level majoring in Mechanical Engineering (27 participants educate), with type study experiment, one group pretest-posttest design. retrieval technique sample that is simple random sampling. Data analysis techniques are carried out qualitative and quantitative. Analysis qualitative conducted to results related to observations and interviews with analysis needs. Whereas analysis quantitative was conducted on data on the feasibility and effectiveness of PBSAS on CPLE lessons in VET School. PBSAS implementation of CPLE lessons at VET School is not yet in accordance with the hope, because students still experience confusion on PBSAS instructions that have not been clear. PBSAS was developed served in google slide form, students could work on the PBSAS to edit it on the slide shared by the teacher and containing material in the form of animated videos. PBSAS on CPLE lessons at VET School has high effectiveness, demonstrated with the value of N Gain score is 0.749 and strong.